Compressibility Characteristics of Undisturbed Snow. - Abele,Gunars; Gow,Anthony J. (1975)
The effects of snow temperature, rate of deformation, and initial density on the stress vs density and stress vs deformation relationships were investigated in the pressure range of 0.1 to 75 bars. The rate of deformation in the range of 0.027 to 27 cm/sec does not have a significant effect. A decrease in temperature in the range of 0 to -40C increases the resistance to stress and deformation, the temperature effect increasing with applied pressure and initial density. The effect of initial density is significant. For any stress, an increase in the initial density results in an incrase in the resulting density, particularly at low stress levels and at temperatures near 0C. The texture of artifically compacted snow is significantly different from that of naturally compacted snow of the same density because of the very short recrystallization time period.